Children’s Rights and the Criminal Protection of Minors - Váradi-Csema, Erika (Criminal Legal Studies: European Challenges and Central European Responses in the Criminal Science of the 21st Century, 2022)
The development of the criminal law protection of minors relates to the rise of children’s rights. Even today, this area of law exerts one of the most powerful effects on juvenile criminal justice. It also serves as a filter through which the quality of the regulations regarding minor offenders and victims can be measured. Therefore, the study examines the topic of children’s rights, primarily its evaluative aspect. It discusses the facts related to the suppressing of attacks against minors and the rules for juvenile offenders in the complex review of the criminal law rules affecting minors. Common historical influences play an important role in the development of the criminal policy of Central and East-Central European countries. Belonging to the Soviet era and the socialist state system provided a common ideological framework for the attitude toward young offenders and for defining the framework of, for example, parental rights and educational tools. The political change in each country caused a serious social cataclysm, which sometimes induced the development of a more marked penal policy and the need for more decisive action against juvenile offenders. Meanwhile, international documents played an important role in the spread of new alternative or community sanctions. The accession to the Council of Europe and later to the EU brought the noted countries back into a common framework. The study focuses on the CEE-countries, and aims to provide a general overview, from a historical perspective, of the development of children’s rights and criminal justice.KEYWORDS: children’s rights, criminal policy, juvenile justice, criminal policy tools, CEE countries